Relationship between Biofilm Production and High Somatic Cell Count in Streptococcus agalactiae Isolated from Milk of Cows with Subclinical Mastitis - Bonsaglia, Erika Carolina Romão [UNESP]; Rossi, Rodolfo S. [UNESP]; Latosinski, Giulia [UNESP]; Rossi, Bruna Fernanda [UNESP]; Campos, Fernanda Cristina [UNESP]; Junior, Ary Fernandes [UNESP]; Pantoja, José Carlos F. [UNESP]; Rall, Vera Lucia Mores [UNESP] (MDPI, 2023)
Streptococcus agalactiae (S. agalactiae) is one of the main agents that causes mastitis in dairy cows, mainly inducing the subclinical form, which is characterized by a high somatic cell count (SCC). The aim of this study was to correlate the increase in SCC caused by S. agalactiae in cows with subclinical mastitis to the presence of genes related to adhesion and invasion in bovine mammary epithelial cells (BMEC) and biofilm formation. Considering the 145 isolates tested, 57.2% presented the capsular type Ia and 42.8% presented type III. We identified the virulence genes among the isolates and determined nine genetic profiles. The most common profile was identified in 69 isolates (47.5%): Ia, fbsA+, fbsB-, pI1-, pI2a-, pI2b+, and hylb+. All isolates produced biofilm, with 58.6% classified as strong producers, 29% as moderate producers and 12.4% as weak producers. No statistical correlation was found between the presence of virulence genes and increased SCC or biofilm production. However, biological evidence was observed between increased SCC and biofilm production. One isolate from each profile was randomly subjected to adhesion and invasion assays, and all of them adhered to BEMC, but none were able to invade. Our results showed that different genetic profiles do not provide advantages for bacteria to invade BMEC in vitro. In addition, biofilm production appears to be related to high SCC.
Keywords: biofilm; capsular type; mastitis; SCC; Streptococcus agalactiae